The troubadour of the basement and his little map of time: possible articulations between the teaching of geographical categories and Belchior’s work - Araújo Coutinho de Paula, Larissa; Fuini, Lucas Labigalini (Geografares, 2025)
The article in question aims to analyze the lyrics of songs by Ceará singer-songwriter Antônio Carlos Belchior (1946-2017), in the light of the main geographical categories: space, territory, region, landscape, and place. The paper was prepared using methodological procedures such as a bibliographic and documentary review on the use of music as a teaching resource, geographical categories in geography teaching, and the artist’s biographies. Subsequently, a survey of his compositions was carried out, and based on reading and systematization, possible relationships between each geographical category and his works were identified. Finally, an in-depth analysis of selected songs and their contributions to geography teaching was proposed. Thus, it can be concluded that the use of music in geography teaching contributes to the appreciation of Brazilian culture, broadens students’ linguistic repertoire, and encourages the development of a critical and analytical view of both national culture and Brazilian geography itself.